2020
DOI: 10.1089/whr.2020.0040
|View full text |Cite
|
Sign up to set email alerts
|

Patient Understanding of Uterine Fibroids and the Different Surgical Approaches to Hysterectomy

Abstract: Objective: The purpose of this study was to assess understanding of the hysterectomy procedure and uterine fibroids among women in a general gynecology clinic. Materials and Methods: This was an anonymous cross-sectional survey. We adapted and pilot tested a survey instrument designed to assess understanding of the hysterectomy procedure and of uterine fibroids. The final version of the survey consisted of basic demographic questions, followed by 28 knowledge questions (Canadian Task Force Classification II-2)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…An anonymous population-based survey was distributed to women in a study designed to assess understanding of hysterectomies and uterine fibroids and included 28 knowledge questions and ten demographic questions. The knowledge questions focused on hysterectomy indications, hysterectomy types, procedures, post-hysterectomy care, and complications ( 5 ). A total of 200 surveys were collected.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…An anonymous population-based survey was distributed to women in a study designed to assess understanding of hysterectomies and uterine fibroids and included 28 knowledge questions and ten demographic questions. The knowledge questions focused on hysterectomy indications, hysterectomy types, procedures, post-hysterectomy care, and complications ( 5 ). A total of 200 surveys were collected.…”
Section: Resultsmentioning
confidence: 99%
“…Belilovets ( 5 ) reported that over 20 million women had undergone a hysterectomy. Hysterectomy is the most performed gynecological surgery.…”
Section: Introductionmentioning
confidence: 99%
“…Comparable research was conducted and reported that the educated population's comprehension of hysterectomy surgery and fibroids, in general comprehension was poor. The numerous methods of performing a hysterectomy and uterine fibroids were particular areas where expertise was lacking 9 .…”
Section: Discussionmentioning
confidence: 99%
“…Due to the longer operating times but shorter hospital stays associated with minimally invasive surgery, the overall hospital cost is similar. The optimal surgical route is determined by multiple factors, including uterine size, accessibility, mobility, adhesions, uterine shape, uterine pathology, and surgeon experience 9 .…”
Section: Introductionmentioning
confidence: 99%